Dependence of Microcrack Behavior in Wood on Moisture Content during Drying - Hiroyuki Yamamoto; Hiroki Sakagami; Yoshio Kijidani; Junji Matsumura (Advances in Materials Science and Engineering)
A modified confocal laser scanning microscopy (CLSM) system was developed not only to observe the microcracks on the surface of Cryptomeria japonica D. Don in situ at the cellular level but also to obtain information about the moisture content (MC) of the wood surface by measuring the change in its electrical resistivity. The sequential images and changes in the electrical resistivity of the wood surface indicated that microcracks formed between the tracheid and ray parenchyma in the latewood region at >1.0E + 07 Ω/sq (square). Microcracks formed when the MC of the wood surface was below the fiber saturation point determined through regression analysis of the surface electrical resistivity and MC. Most of the microcracks develop when the surface electrical resistivity ranged from 3.95E + 10 to 3.60E + 12 Ω/sq. When the surface MC was ~2.5%, microcracks closed and the surface electrical resistivity was either ~1.00E + 15 Ω/sq or outside the measurement range. The modified CLSM and the method to measure the MC of the wood surface can be used to acquire information about the surface MC in specific areas shown in CLSM images. The findings indicated that the MC of the surface of the wood plays an important role in suppressing the emergence of microcracks in drying wood. The modified CLSM system and the method of measuring the MC of the surface of wood can be used to efficiently evaluate methods of drying wood and the quality of dried wood.